2016
DOI: 10.1111/all.13031
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus components distinguish IgE but not IgG4 profiles between fungal sensitization and allergic broncho-pulmonary aspergillosis

Abstract: Aspergillus fumigatus is the causative agent of allergic broncho-pulmonary aspergillosis. Prompt and accurate diagnosis may be difficult to achieve with current clinical and laboratory scores, which do not include immune responses to recombinant A. fumigatus allergens. We measured specific immunoglobulin E and G4 directed to recombinant A. fumigatus allergens in 55 cystic fibrosis patients without allergic broncho-pulmonary aspergillosis but sensitized to A. fumigatus and in nine patients with allergic broncho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Current reports on IgG responses to commercially available allergens from A. fumigatus are scarce and address mainly ABPA patients with an asthmatic background . Our team found that IgG4 responses to A. fumigatus allergens did not distinguish between A. fumigatus ‐sensitized CF patients and active ABPA . A first step toward an integrated IgE and IgG workup might be the use of a single method for head‐to‐head comparison.…”
Section: Component‐resolved Diagnostics: Molecular Aspects Of the Hummentioning
confidence: 95%
See 4 more Smart Citations
“…Current reports on IgG responses to commercially available allergens from A. fumigatus are scarce and address mainly ABPA patients with an asthmatic background . Our team found that IgG4 responses to A. fumigatus allergens did not distinguish between A. fumigatus ‐sensitized CF patients and active ABPA . A first step toward an integrated IgE and IgG workup might be the use of a single method for head‐to‐head comparison.…”
Section: Component‐resolved Diagnostics: Molecular Aspects Of the Hummentioning
confidence: 95%
“…This explains the tentative proposal of “a raised level of sIgE to A. fumigatus ” in more recent papers. Abundant experimental data support this view, but a widely validated threshold is lacking. Disparate cutoff values have been reported in the literature, from 1.91 kUA/L to “class 2 or more” to 29.8 kUA/L .…”
Section: Why Should Immunological Criteria For Abpa Diagnosis Be Updamentioning
confidence: 99%
See 3 more Smart Citations